Psychological correlates of disordered eating in youth with type 1 diabetes: Results from diabetes MILES Youth—Australia. Issue 4 (11th March 2020) - Araia, Emanuala; King, Ross M.; Pouwer, Frans; Speight, Jane; Hendrieckx, Christel
Abstract: Background: This study examined the relationship between disordered eating (DE), body dissatisfaction (BD), and psychological variables; and identified correlates of DE in youth with type 1 diabetes. Methods: Data were from the Diabetes Management and Impact for Long‐Term Empowerment and Success Youth Study—Australia, an online survey assessing the psychosocial impact of type 1 diabetes. Adolescents (N = 477; mean age 16 ± 2 years) with type 1 diabetes for at least 1 year, completed the Diabetes Eating Problem Survey‐Revised, measures of BD, quality of life, well‐being, depressive and anxiety symptoms, diabetes distress, and resilience. Results: DE correlated positively (moderate‐large) with depressive and anxiety symptoms, diabetes distress, and BD; and negatively (moderate‐large) with well‐being, quality of life, and resilience. In contrast, BD correlated (moderately) with all psychological variables in females only. In the stepwise regression, high diabetes distress and BD were the strongest predictors of DE. While the magnitude of BD was almost five times higher in females, the level of DE risk across genders did not differ when BD was added into the model, which overall explained 71% of the variance. Conclusions: This study explored potential risk and protective factors associated with DE. The novel finding that diabetes distress is a strong indicator of DE provides preliminary support for its inclusion into future risk models and potential target for intervention. Longitudinal studies are required to map how these factors predict changes over time with greater emphasis needed into understanding the gender‐specific risks associated with BD, particularly during more difficult developmental phases, such as adolescence to young adulthood.